Shared prosperity in America's communities - Ding, Lei, 1974-; Wachter, Susan M. (City in the twenty-first century book series., 2016)
Shared Prosperity in America's Communities examines the degree to which place matters in the geography of economic opportunity; offers strategies to address the challenges of place-based inequality; and shows how communities across the nation are implementing change and building a future of shared prosperity.